2020
DOI: 10.1021/acs.langmuir.0c01851
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability and Miscibility in Ethanol/AOT/n-Heptane Systems: Evidence of Multilayered Cylindrical and Spherical Microemulsion Morphologies

Abstract: We describe the effects of ethanol on the phase behavior of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) in nheptane. Using dynamic light scattering (DLS), molecular dynamics (MD) simulations, and nuclear magnetic resonance ( 1 H NMR) spectroscopy, we investigate the aggregation behavior of AOT across a wide range of ethanol/AOT/n-heptane compositions. We conclude that reverse micelles do not form at any of the investigated concentrations. Instead, we observe the formation of other surfactant aggregate morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
2
3
0
Order By: Relevance
“…This elongation of droplets might be also influenced by the use of n-pentanol in the oil phase, as a cosurfactant effect of alcohols localized at microemulsion interfaces. 36 Note that already MNPs alone can induce droplet−droplet attractions as already demonstrated in earlier investigations. 23 On the other hand, the polycation shell of Au(PEI)NPs can influence the spontaneous curvature of the AOT surfactant film through electrostatic interactions 37 and, therefore, modify the microemulsion morphology.…”
Section: ■ Results and Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This elongation of droplets might be also influenced by the use of n-pentanol in the oil phase, as a cosurfactant effect of alcohols localized at microemulsion interfaces. 36 Note that already MNPs alone can induce droplet−droplet attractions as already demonstrated in earlier investigations. 23 On the other hand, the polycation shell of Au(PEI)NPs can influence the spontaneous curvature of the AOT surfactant film through electrostatic interactions 37 and, therefore, modify the microemulsion morphology.…”
Section: ■ Results and Discussionsupporting
confidence: 57%
“…Cryo-SEM micrographs after 1 week of phase separation provide a clearer insight of the L 2 phase modulation, indicating an elongation of microemulsion droplets in the presence of both nanoparticles into cylindrical, wormlike structures (Figure ). This elongation of droplets might be also influenced by the use of n -pentanol in the oil phase, as a cosurfactant effect of alcohols localized at microemulsion interfaces . Note that already MNPs alone can induce droplet–droplet attractions as already demonstrated in earlier investigations .…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…While this equation does not predict the point of instability with respect to salt additions, its reliance on only three variablescation valency, cation concentration (related through the Debye screening length), and the anion hydrated radiusdoes point toward ion hydration being an important factor to consider for reverse micelle stability. In the current report, we further analyze the reverse micelle size data collected by dynamic light scattering (DLS) on water/AOT/isooctane systems of w 0 = 10 with the addition of NaBH 4 , FeSO 4 , Mg­(NO 3 ) 2 , CuCl 2 , Al­(NO 3 ) 3 , Fe­(NO 3 ) 3 , and Y­(NO 3 ) 3 , in conjunction with published data on ion hydration and reverse micelle water dynamics. We propose new model mechanisms for reverse micelle instability and develop an equation for predicting critical salt concentrations for reverse micelle instability.…”
Section: Introductionmentioning
confidence: 99%
“…13,58,63 The findings can be expected to generalize to AOT aggregation in the absence of water, especially if other polar impurities or additives are present. For example, several non-aqueous polar solvents, such as short-chain alcohols, form reverse micelles [120][121][122][123] and act as cosurfactants. 123,124 For example, AOT/non-polar solvent/alcohol tertiary systems have revealed that alcohol molecules, such as methanol, not only bind to AOT headgroups, but can also solvate AOT hydrocarbon tails and disperse in the apolar solvent phase.…”
Section: Resultsmentioning
confidence: 99%